2000
DOI: 10.1007/s007920070011
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the polar lipid and pigment profiles of two solar salterns located in Newark, California, U.S.A., and Eilat, Israel

Abstract: The whole community pigments and lipids have been examined during a 5-year period in two commercial solar salterns located in the United States and in Israel. There were significant differences in the complexity of the lipid and pigment patterns within the California saltern system, and these differences were not consistent over the sampling period despite examination of ponds with the same salinity. The solar saltern system in Eilat, Israel, showed greater consistency during this sampling period and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…Among the selected saltwork, the crystallizer ponds had higher halobacterial biomass when compared to reservoir and condenser ponds. The observations pertaining to the incidence of high halobacterial densities in crystallizer pond in the present study correlated with earlier investigations, which include Oren (1990), Litchfield et al, 2000 andTamerkisspapo (2000). Litchfield et al, 2000 had remarked that the biodiversity of saltern is due to the seasonal differences in an ecosystem.…”
Section: G Total Halobacterial Density In the Brine Samples And Wet supporting
confidence: 92%
“…Among the selected saltwork, the crystallizer ponds had higher halobacterial biomass when compared to reservoir and condenser ponds. The observations pertaining to the incidence of high halobacterial densities in crystallizer pond in the present study correlated with earlier investigations, which include Oren (1990), Litchfield et al, 2000 andTamerkisspapo (2000). Litchfield et al, 2000 had remarked that the biodiversity of saltern is due to the seasonal differences in an ecosystem.…”
Section: G Total Halobacterial Density In the Brine Samples And Wet supporting
confidence: 92%
“…Further, the prokaryotic community in the higher temperature crystallizer (27 to 40°C) in our eutrophic saltern might have a different composition than that in the oligotrophic Eilat saltern. Comparisons of the polar lipid and metabolic profiles of 2 eutrophic solar salterns located in Newark, California, USA, and in the oligotrophic saltern at Eilat, Israel, con- Table 1 sistently showed such regional differences in the microbial communities in summer (Litchfield et al 2000(Litchfield et al , 2001. One intriguing observation was that PHP was betaine limited only during the summer (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Javor (1983) showed that tropical salterns had less chlorophyll a (chl a) and fewer nutrient variations than similar systems located in the temperate zone. Based on comparisons of the polar lipid and metabolic profiles of 2 solar salterns in Newark, California, USA, and Eilat, Israel, Litchfield et al (2000Litchfield et al ( , 2001) noted seasonal differences in the saltern microbial communities. However, seasonal studies on prokaryotic growth-related variables along a salinity gradient have not been made (Gasol et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance profile of nonpolar lipids showed that, relative to the background strain, SRP19-lacking cells presented major absorption peaks at 490 nm and 530 nm (Fig. 3A), likely corresponding to bacterioruberin (17). Elevated bacterioruberin levels are noted in haloarchaea facing various stress conditions (3,8,10,15,20,24).…”
mentioning
confidence: 96%